Part object, part sculpture - Molesworth, Helen; Wexner Center for the Arts at The Ohio State University, Columbus (Columbus : Pennsylvania State University Press Pennsylvania Wexner Center for the Arts, The Ohio State University Columbus, 2005)
Benglis, Lynda ; Bontecou, Lee ; Bourgeois, Louise ; Broodthaers, Marcel ; Burri, Alberto ; Duchamp, Marcel ; Fontana, Lucio ; Gober, Robert ; Gonzalez-Torres, Felix ; Hesse, Eva ; Johns, Jasper ; Kusama Yayoi ; Manzoni, Piero ; McCollum, Allan ; McElheny, Josiah ; Nauman, Bruce ; Orozco, Gabriel ; Rauschenberg, Robert ; Twombly, Cy ; Whiteread, Rachel
Bibliog. p. 278-279
Publication on the occasion of the exhibition 'Part object, part sculpture' at the Wexner Center for the Arts at The Ohio State University in Columbus, 30.10.2005-26.02.2006
boek